A new Rindera (Boraginaceae) species from Western Anatolia, Turkey - Yildirim, Hasan (Phytotaxa, 2019)
Rindera cetineri Yıldırım (Boraginaceae) is described here as a new species. Diagnostic morphological characters, a full description, and detailed illustrations are given herein. Rindera cetineri is restricted to the Akdağ Mountain in the Çameli district of the province of Denizli in western Anatolia, Turkey. It shows morphological similarities to Rindera lanata, Rindera graeca, Rindera caespitosa, and Rindera dumanii. It is easily distinguished from these species, especially by its linear to linear lanceolate and light pinkish-purple with darker striation lobes; corolla lobes divided into 2/5–1/2 corolla lenght; anther shorter than lobes.